Design of Interactions Between Nanomaterials and Proteins: A Highly Affine Peptide Tag to Bare Iron Oxide Nanoparticles for Magnetic Protein Separation. Issue 3 (9th May 2018) - Schwaminger, Sebastian P.; Blank‐Shim, Silvia A.; Scheifele, Isabell; Pipich, Vitaliy; Fraga‐García, Paula; Berensmeier, Sonja
Abstract : Superparamagnetic nanoparticles have recently gained much attention due to their broad range of applicability including medical in vivo technologies, sensors, and as supports for catalysts. As magnetic affinity materials, they can be utilized for the development of new purification strategies for pharmaceuticals and other target molecules from crude lysates. Here, a short peptide tag based on a glutamate sequence is introduced and the adsorption of pure protein as well as protein from crude cell lysate at different conditions is demonstrated. Fused to a model protein this tag can be used to recognize and purify this protein from a fermentation broth by bare iron oxide nanoparticles (BIONs). Binding of up to 0.2 g protein per g nanoparticles can be achieved and recovered easily by switching to a citrate buffered system. For a deeper understanding of the separation process, the aggregation and agglomeration of the nanoparticle protein systems were monitored for binding and elution steps. Furthermore, an upscaling of the process to the liter scale and the separation of a green fluorescent protein (GFP) containing the affinity tag to purities of 70% from Escherichia coli fermentation broth was possible in a one step process by means of high gradient magnetic separation (HGMS). Abstract : A promising novel iron oxide binding tag consisting of glutamate subunits facilitates the separation and purification of proteins by bare iron oxide nanoparticles (BIONs). The tag can be fused to proteins and allows a coordinative binding to the iron oxide surface. The reversible binding of a model protein from Escherichia coli fermentation broth is even applicable in the liter scale.